Разработка системы мониторинга получения кислородсодержащих соединений кобальта плазмохимическим методом - Сергеева, Ольга Вячеславовна; Пивоваров, Александр Андреевич; Пиляев, Валентин Валентинович (НТУ "ХПИ", 2016)
В данной работе рассматривалась система мониторинга процесса получения обводненных кислородосодержащих соединений кобальта с использованием плазмохимического реактора. Перспективы использования подобных систем связаны с появлением тенденции к развитию мини производств, специализирующихся на производстве специальных химических веществ, а также сыпучих промежуточных веществ, пользующихся устойчивым спросом. Отмечено, что использование системы мониторинга для технологий с использованием плазмохимических процессов в условиях экспериментально-исследовательской лаборатории, совмещенной с мини производством, позволяет существенно сократить время на сокращение исследований за счет снятия комплекса показаний соотнесенных с реальным временем процесса.

This paper discusses the system of monitoring the process of obtaining oxygen-containing compounds of cobalt using plasma chemical reactor. Prospects for the use of such systems are associated with the emergence of the trend towards the development of small enterprises, specializing in the production of specialty chemicals and bulk intermediates are in steady demand. It should be noted that the use of monitoring systems for technologies using plasma-chemical processes in the conditions of experimental research laboratories, coupled with a small production, can significantly reduce the time to research by recording the readings in real-time process. The use of computer monitoring system in small industries (laboratories), combined with experimental studies is a great help to maximize the use of existing equipment. This is especially true for the development of technology-based contact using the nonequilibrium low-temperature plasma.
Development of monitoring system for producing oxygen-containing compounds of cobalt by plasmo-chemical method
Keywords: неравновесная плазма; жидкость; наноразмерные соединения; мини-производства; nonequilibrium plasma; liquid; nano-sized compounds